2020
DOI: 10.3389/fpls.2020.00263
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Chloroplast Sequences Resolve the Enigmatic Origin of the Concord Grape

Abstract: Despite the commercial importance of the Concord grape, its origin has remained unresolved for over 150 years without a comprehensive phylogenetic analysis. In this study we aimed to reconstruct the evolutionary history of the Concord grape using sequence data from four nuclear markers (AT103, GAI1, PHYA, and SQD1), six plastid markers (matK, psbA-trnH, petN-trnC, ycf1, trnL-F, and trnS-G), and the plastid genome. We sampled extensively the Vitis species native to northeastern North America as well as represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…Given the cytonuclear discordance of the phylogenetic position of this V. labrusca sample from Ma et al (2018) and the evidence listed below, it is highly likely that the particular sample was a hybrid. This particular tissue sample of V. labrusca was obtained as a cultivar in Henan, China as indicated by Ma et al (2018), and it may be a horticulture hybrid between V. labrusca and V. vinifera , likely the Concord grape, which is known as Vitis × labruscana L.H.Bailey (Moore & Wen, 2016; Wen et al, 2020). Furthermore, the phyparts analyses showed that only 72 SCNs supported the sister relationship between this V. labrusca sample and V. vinifera , contrasting to the 196 conflicting SCNs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the cytonuclear discordance of the phylogenetic position of this V. labrusca sample from Ma et al (2018) and the evidence listed below, it is highly likely that the particular sample was a hybrid. This particular tissue sample of V. labrusca was obtained as a cultivar in Henan, China as indicated by Ma et al (2018), and it may be a horticulture hybrid between V. labrusca and V. vinifera , likely the Concord grape, which is known as Vitis × labruscana L.H.Bailey (Moore & Wen, 2016; Wen et al, 2020). Furthermore, the phyparts analyses showed that only 72 SCNs supported the sister relationship between this V. labrusca sample and V. vinifera , contrasting to the 196 conflicting SCNs.…”
Section: Discussionmentioning
confidence: 99%
“…The incongruence detected between our plastid result and these two nuclear topologies may be due to the hybridization events during the diversification of the Yulania and Michelia clades and their close relatives. Hybridizations have played an important role in the evolution of Magnoliaceae (Kim et al, 2019) and many other lineages of angiosperms (Wen et al, 2018(Wen et al, , 2020Liu et al, 2019Liu et al, , 2020aLiu et al, , 2020b.…”
Section: Tulipastrummentioning
confidence: 99%
“…Moreover, there is little knowledge about the phylogenetic relationships between V. vinifera and other grapes. Some authors have proposed the origin of an ancient Eurasian clade [79,85] and V. jacquemontii R. Parker could be the sister species of V. vinifera [88]. The identification and characterisation of closely related wild grapes can have important repercussions also from an agronomic perspective.…”
Section: Plastid Dna To Explore the Maternal Lineagesmentioning
confidence: 99%
“…Moreover, incomplete lineage sorting [ 81 ] or introgression [ 73 ] could have confuse phylogeny between close relatives. An increasing number of plastid DNA sequences were used to explain the evolution of some Vitis taxa [ 79 , 82 , 83 , 84 ] as well as to support the reconstruction of the pedigree of some cultivars [ 85 ]. Today, next-generation sequencing technologies offer an unprecedented access to complete genome sequences and to investigate the plastomes has been proven to be a good procedure to infer new evolutive lines [ 86 , 87 ].…”
Section: Plastid Dna To Explore the Maternal Lineagesmentioning
confidence: 99%